Fra Jagannātha til juggernaut: Billedkult og kristen mission ved den store vognprocession i Puri - Mikael Aktor (Religionsvidenskabeligt Tidsskrift, 2017)
English abstract: The Car Festival in Puri, Odisha, is one of the world’s largest religious processions. About one million pilgrims follow the three god-siblings, Jagannātha, Subhadrā and Balabhadra, each seated in their own gigantic procession chariot pulled by hundreds of pilgrims, on their journey from the main Jagannātha temple to the Guṇḍicā temple three kilometers away. The perception of this procession festival by the British missionaries in Odisha during the first half of the 19th century was the background for the linguistic transformation whereby the name of a god, Jagannātha, became the notion of an overwhelming destructive force, ‘juggernaut’. The article examines the history of this transformation by a reading of quotes from foreign travelers to Odisha during the 14th through the 19th century. It also offers a description of the procession rituals, a reflection on the general characteristics of religious processions, and a discussion of the ‘idolatry’ discourse that lies behind the linguistic transformation from ‘Jagannātha’ to ‘juggernaut’.